The fortune seller eaudiobook A novel. - Kapelke-Dale, Rachel (Macmillan Audio, 2024)
Yellowjackets meets The Cloisters in this beguiling coming-of-age story about class, reinvention, and destiny, set against the backdrop of two mysterious deaths. Middle-class Rosie Macalister has worked for years to fit in with her wealthy friends on the Yale equestrian team. But when she comes back from her junior year abroad with newfound confidence, she finds that the group has been infiltrated by a mysterious intruder: Annelise Tattinger. A talented tarot reader and a brilliant rider, the enigmatic Annelise is unlike anyone Rosie has ever met. But when one of their friends notices money disappearing from her bank account, Annelise's place in the circle is thrown into question. As the girls turn against each other, the group's unspoken tensions and assumptions lead to devastating consequences. It's only after graduation, when Rosie begins a job at a Manhattan hedge fund, that she uncovers Annelise's true identity––and how her place in their elite Yale set was no accident. Is it too late for Rosie to put right what went wrong, or does everyone's luck run out at some point? Set in the heady days of the early aughts, The Fortune Seller is a haunting examination of class, ambition, and the desires that shape our lives. A Macmillan Audio production from St. Martin's Press.